High-strength multilayer thermal insulation material and preparation method thereof

By using phenolic fiber, zirconia fiber, alumina nanosheets and phosphate solution, combined with papermaking and carbonization processes, and introducing potassium hexatitanate K2Ti6O13 nanowires, we have solved the problem of high-temperature and long-term application of existing high-temperature-resistant multi-layer insulation materials. To solve the problems of medium strength and easy structural failure, multi-layer insulation materials with high strength and excellent thermal insulation performance have been realized.

CN119348273AActive Publication Date: 2025-01-24AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411460227.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

In the long-term application of high temperature resistant multi-layer insulation materials, the material strength and structure are prone to failure, and the shear resistance is insufficient, which cannot meet the insulation and mechanical requirements in extreme environments such as aircraft.

Method used

Using phenolic fiber, zirconia fiber, alumina nanosheets and phosphate solution as the main materials, through papermaking and carbonization processes, a high-strength multi-layer insulation material is constructed, and potassium hexatitanate K2Ti6O13 nanowires are introduced into the material to enhance the strength. and thermal insulation properties.

Benefits of technology

It significantly improves the strength and thermal insulation performance of the material, enhances the fiber overlap and adhesive area, improves the interface effect between oxidation fiber and phenol fiber, and ensures the stability and efficient insulation of the material in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091659390000151
    Figure BDA0005091659390000151
Patent Text Reader

Abstract

The invention relates to a high-strength multilayer thermal insulation material and a preparation method thereof. The method comprises the following steps: uniformly dispersing phenolic fibers, zirconia fibers, alumina nanosheets and a phosphate solution with water to obtain a dispersion system; porous phenolic fiber cloth is flatly laid in paper making equipment to serve as a filtering medium, then the dispersed system is subjected to paper making through the paper making equipment where the porous phenolic fiber cloth is flatly laid, and a prefabricated body is obtained; the prefabricated body comprises porous phenolic fiber cloth and a papermaking material obtained on the porous phenolic fiber cloth; and laying the multiple layers of preforms in a shaping mold layer by layer for shaping and drying, and carbonizing in an inert atmosphere to prepare the high-strength multi-layer thermal insulation material. According to the invention, the traditional interface effect of the reflecting screen and the zirconium oxide fiber is effectively solved, the mechanical strength of the multilayer thermal insulation material is greatly improved, and a solid material foundation is laid for the application of the multilayer thermal insulation material in an extreme environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zirconium oxide fiber thermal insulation materials, and in particular relates to a high-strength multi-layer thermal insulation material and a preparation method thereof. Background Art

[0002] As various aerospace vehicles develop towards high Mach numbers and long flight times, they face increasingly harsh thermal environments, which puts forward new requirements for thermal insulation materials. High-temperature resistant multi-layer thermal insulation materials, due to their excellent high-temperature thermal insulation performance, show great advantages in the thermal protection structure of flight systems.

[0003] At present, high-temperature resistant multi-layer thermal insulation materials are mainly made of zirconium oxide or aluminum oxide fibers as fiber layers, and carbon-based reflective screens such as composite graphite, carbon fiber cloth or silicon carbide in the middle. Among them, the spacer layer and the fiber layer are bonded by high-temperature resistant adhesive, the interlayer adhesive effect is poor, the material's shear resistance is insufficient, and due to the insufficient matching degree of thermal properties between carbon-based materials and inorganic oxide materials, the material's compressive strength is also greatly insufficient, resulting in the material's strength and structure being easily failed during long-term high-temperature application. Therefore, it is necessary to design and develop new high-strength multi-layer thermal insulation materials to ensure the thermal insulation performance of the material while effectively improving the material's mechanical strength.

[0004] In summary, it is very necessary to provide a high-strength multi-layer thermal insulation material and a preparation method thereof. Summary of the invention

[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a high-strength multi-layer thermal insulation material and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing a high-strength multi-layer thermal insulation material, the method comprising the following steps:

[0007] (1) uniformly dispersing phenolic fiber, zirconium oxide fiber, aluminum oxide nanosheets and phosphate solution with water to obtain a dispersed system;

[0008] (2) laying a porous phenolic fiber cloth flat in a papermaking device as a filter medium, and then papermaking the dispersed system through the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth;

[0009] (3) The multi-layer preform is laid layer by layer in a shaping mold for shaping and drying, and then carbonized under an inert atmosphere to obtain a high-strength multi-layer thermal insulation material.

[0010] Preferably, in step (1): the mass ratio of the zirconium oxide fiber to the phenolic fiber is (4-19):1; the mass ratio of the aluminum oxide nanosheets to the phosphate solution is (1-4):(1-9); and / or the phosphate solution is an aluminum dihydrogen phosphate solution, and the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 20-50%.

[0011] Preferably, in step (1): the diameter of the zirconium oxide fiber is 1 to 10 μm; and / or the diameter of the phenolic fiber is 200 to 1000 nm.

[0012] Preferably, in step (1), the dispersion speed is 4000-10000 r / min, and the dispersion time is 3-40 min.

[0013] Preferably, in step (2): the pore size of the porous phenolic fiber cloth is 500 nm to 2 μm; and / or the thickness of the porous phenolic fiber cloth is 10 to 200 μm.

[0014] Preferably, the thickness of a single layer of the preform is 0.5 to 2 mm; and / or the thickness of the high-strength multi-layer thermal insulation material is 15 to 25 mm.

[0015] Preferably, in step (3): the temperature of the shaping and drying is 200°C to 300°C.

[0016] Preferably, in step (3), the carbonization temperature is 500-900° C., and the carbonization time is 10-20 h.

[0017] Preferably, in step (1): potassium hexatitanate K2Ti6O is also added to the dispersed system 13 Nanowires; preferably, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowires to the aluminum oxide nanosheets is 1:(1-2).

[0018] In a second aspect, the present invention provides a high-strength multi-layer thermal insulation material produced by the preparation method described in the first aspect of the present invention.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] (1) The present invention uses zirconium oxide fiber and phenolic nanofiber as the main materials, and introduces alumina nanosheets and phosphate (aluminum dihydrogen phosphate) solution adhesives to effectively improve the fiber overlap and bonding area, thereby improving the strength of the material; at the same time, the present invention uses phenolic nanofiber as a flexible unit, and forms carbon nanofibers through carbonization. The carbonization process effectively improves the interface effect between zirconium oxide fiber and phenolic fiber, thereby improving the strength and flexibility of the composite material; in addition, the present invention uses porous phenolic fiber cloth as a precursor of the reflective screen, and constructs a densified carbon-based reflective screen through a hot pressing-assisted later carbonization process. This method effectively solves the traditional interface effect between the reflective screen and the zirconium oxide fiber, greatly improves the mechanical strength of the multi-layer thermal insulation material, and lays a solid material foundation for the application of the multi-layer thermal insulation material in extreme environments.

[0021] (2) In some preferred technical solutions of the present invention, potassium hexatitanate K2Ti6O is also introduced into the material. 13 Nanowires, the present invention found that the K2Ti6O 13 The introduction of nanowires helps to further improve the strength, flexibility and thermal insulation performance of high-strength multi-layer thermal insulation materials; the possible reason is that K2Ti6O 13 The fibrous structure of nanowires gives them very high tensile strength and can play a role in skeleton reinforcement in composite materials. 13 Nanowires can be evenly distributed throughout the material matrix to form a dense reinforced network structure, which can effectively block crack propagation, enhance the overall strength of the material, and fill the micropores or gaps that may exist in the material, making the material structure more compact and effectively reducing defects in the material. 13 The nanometer size and aspect ratio of the nanowires give them good flexibility, which can form a good interaction with the matrix material, thereby improving the strength and flexibility of the material. 13 The fiber structure of nanowires can prevent the rapid propagation of cracks in the material. This crack-blocking effect can also significantly improve the fracture toughness of the material. Even under external stress, the material is not prone to brittle fracture, thereby enhancing its flexibility. In addition, K2Ti6O 13 The introduction of nanowires can also improve the thermal insulation performance of high-strength multi-layer thermal insulation materials, K2Ti6O 13 The fibrous structure of nanowires can form a complex three-dimensional network in the material, effectively blocking the heat conduction path. This network structure limits the conduction of heat inside the material, which is beneficial to improve the thermal insulation performance of the material. 13 Nanowires have a certain blocking effect on infrared radiation, reducing infrared radiation, lowering the thermal conductivity of insulation materials, and effectively enhancing the thermal insulation properties of the materials. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In a first aspect, the present invention provides a method for preparing a high-strength multi-layer thermal insulation material, the method comprising the following steps:

[0024] (1) using water to uniformly disperse phenolic fiber, zirconium oxide fiber, aluminum oxide nanosheets and phosphate solution to obtain a dispersion system; in the present invention, the sum of the mass percentages of phenolic fiber, zirconium oxide fiber, aluminum oxide nanosheets and phosphate in the dispersion system may be, for example, 8 to 25%; the present invention does not specifically limit the sources of phenolic fiber, zirconium oxide fiber, aluminum oxide nanosheets, etc., and products that can be directly purchased or prepared by existing methods may be used;

[0025] (2) laying a porous phenolic fiber cloth (porous phenolic fiber cloth) flat in a papermaking device as a filter medium, and then papermaking the dispersed system through the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and a papermaking material obtained on the porous phenolic fiber cloth; the present invention does not specifically limit the papermaking, which is a conventional technology in the field;

[0026] (3) The multilayer preforms are laid layer by layer in a shaping mold (hot pressing mold) for shaping and drying, and then carbonized under an inert atmosphere to obtain a high-strength multilayer thermal insulation material; when laying layer by layer, the porous phenolic fiber cloth and the papermaking material contained in each preform are arranged alternately; the present invention has no special requirements for the pressure for shaping and drying, that is, the pressure assisted by hot pressing, and those skilled in the art can make a conventional selection, for example, it can be 1 to 2 MPa.

[0027] The present invention uses zirconium oxide fiber and phenolic nanofiber as main materials, and effectively improves the fiber overlap and bonding area and the strength of the material by introducing alumina nanosheets and phosphate (aluminum dihydrogen phosphate) solution adhesives; at the same time, the present invention uses phenolic nanofiber as a flexibility unit and forms carbon nanofiber through carbonization. The carbonization process effectively improves the interface effect between zirconium oxide fiber and phenolic fiber, and improves the strength and flexibility of the composite material; in addition, the present invention uses porous phenolic fiber cloth as a precursor of the reflective screen, and constructs a densified carbon-based reflective screen through hot pressing to assist the later carbonization process. This method effectively solves the traditional interface effect between the reflective screen and zirconium oxide fiber, greatly improves the mechanical strength of the multi-layer thermal insulation material, and lays a solid material foundation for the application of multi-layer thermal insulation materials in extreme environments.

[0028] According to some specific embodiments, the preparation of the high-strength multi-layer thermal insulation material comprises the following steps:

[0029] ①Use porous phenolic fiber cloth as the filter medium and lay it flat on the dispersion-molding (papermaking) integrated equipment;

[0030] ② Weigh a certain mass of phenolic fiber, zirconium oxide fiber, alumina nanosheets and aluminum dihydrogen phosphate solution and add them into the dispersion-molding (papermaking) integrated equipment, start the program to add water for rapid dispersion to obtain a dispersed system, and then paper the dispersed system to obtain a papermaking material on a porous phenolic fiber cloth;

[0031] ③ The papermaking material and the filter medium (porous phenolic fiber cloth) at the bottom are used as a group of preforms, and are laid layer by layer in a hot pressing mold for shaping and drying;

[0032] ④Finally, the above-mentioned shaped and dried materials are placed in an inert atmosphere furnace for carbonization to obtain a high-strength multi-layer thermal insulation material.

[0033] According to some preferred embodiments, in step (1): the mass ratio of the zirconium oxide fiber to the phenolic fiber is (4-19):1 (for example, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1 or 19:1); the mass ratio of the aluminum oxide nanosheets to the phosphate solution is (1-4):(1-9); in the present invention, preferably, the sum of the mass amounts of the aluminum oxide nanosheets and the phosphate solution is 25-60% of the sum of the mass amounts of the phenolic fiber and the zirconium oxide fiber; and / or the phosphate solution is an aluminum dihydrogen phosphate solution, and the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution (i.e., aluminum dihydrogen phosphate aqueous solution) is 20-50%.

[0034] According to some preferred embodiments, in step (1): the diameter of the zirconium oxide fiber is 1 to 10 μm; and / or the diameter of the phenolic fiber (phenolic nanofiber) is 200 to 1000 nm.

[0035] According to some preferred embodiments, in step (1): the dispersion rotation speed is 4000-10000 r / min (for example, 4000, 5000, 6000, 7000, 8000, 9000 or 10000 r / min), and the dispersion time is 3-40 min (for example, 3, 5, 8, 10, 15, 20, 25, 30, 35 or 40 min).

[0036] According to some preferred embodiments, in step (2): the pore size of the porous phenolic fiber cloth is 500nm-2μm (for example, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.2μm, 1.5μm, 1.8μm or 2μm); and / or the thickness of the porous phenolic fiber cloth (i.e., porous phenolic fiber cloth) is 10-200μm (for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 or 200μm); in the present invention, the porosity of the porous phenolic fiber cloth is, for example, 50-70%.

[0037] According to some preferred embodiments, the thickness of a single layer of the preform is 0.5 to 2 mm (for example, 0.5, 1, 1.2, 1.5, 1.8 or 2 mm); and / or the thickness of the high-strength multi-layer thermal insulation material is 15 to 25 mm (for example, 15, 18, 20 or 25 mm); in the present invention, preferably, the thickness of the internal accommodating space of the shaping mold is 15 to 25 mm. In the present invention, the thickness of the internal accommodating space of the shaping mold corresponds to the thickness of the obtained high-strength multi-layer thermal insulation material.

[0038] According to some preferred embodiments, in step (3): the temperature of the shaping and drying is 200°C to 300°C (for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C), and the shaping and drying time is, for example, 12 to 36 hours, preferably 24 hours.

[0039] According to some preferred embodiments, in step (3): the carbonization temperature is 500-900°C (e.g., 500°C, 600°C, 700°C, 800°C or 900°C), and the carbonization time is 10-20h (e.g., 10, 12, 15, 18 or 20h).

[0040] According to some preferred embodiments, in step (1): potassium hexatitanate K2Ti6O is also added to the dispersed system. 13 Nanowires (i.e. K2Ti6O 13 Nanowire); the present invention is to K2Ti6O 13 The source and size of the nanowires are not specifically limited, and can be directly purchased products or products synthesized by existing methods; in the present invention, the potassium hexatitanate K2Ti6O 13 The diameter of the nanowire is, for example, 80 to 120 nm, and the length is, for example, 40 to 50 μm.

[0041] The present invention preferably introduces potassium hexatitanate K2Ti6O into the material. 13 Nanowires, the present invention found that the K2Ti6O 13 The introduction of nanowires helps to further improve the strength, flexibility and thermal insulation performance of high-strength multi-layer thermal insulation materials; the possible reason is that K2Ti6O 13 The fibrous structure of nanowires gives them very high tensile strength and can play a role in skeleton reinforcement in composite materials. 13 Nanowires can be evenly distributed throughout the material matrix to form a dense reinforced network structure, which can effectively block crack propagation, enhance the overall strength of the material, and fill the micropores or gaps that may exist in the material, making the material structure more compact and effectively reducing defects in the material. 13 The nanometer size and aspect ratio of the nanowires give them good flexibility, which can form a good interaction with the matrix material, thereby improving the strength and flexibility of the material. 13 The fiber structure of nanowires can prevent the rapid propagation of cracks in the material. This crack-blocking effect can also significantly improve the fracture toughness of the material. Even under external stress, the material is not prone to brittle fracture, thereby enhancing its flexibility. In addition, K2Ti6O 13 The introduction of nanowires can also improve the thermal insulation performance of high-strength multi-layer thermal insulation materials, K2Ti6O 13 The fibrous structure of nanowires can form a complex three-dimensional network in the material, effectively blocking the heat conduction path. This network structure limits the conduction of heat inside the material, which is beneficial to improve the thermal insulation performance of the material. 13 Nanowires have a certain blocking effect on infrared radiation, reducing infrared radiation, lowering the thermal conductivity of insulation materials, and effectively enhancing the thermal insulation properties of the materials.

[0042] According to some preferred embodiments, the potassium hexatitanate K2Ti6O 13The mass ratio of the nanowires to the alumina nanosheets is 1:(1-2) (e.g., 1:1, 1:1.5 or 1:2); in the present invention, preferably, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowire to the alumina nanosheet is 1:(1-2). The present invention finds that potassium hexatitanate K2Ti6O 13 Nanowires have a large surface area and a reinforcing effect in the material. The amount of nanowires added needs to be controlled within a reasonable range to avoid K2Ti6O 13 The agglomeration of nanowires affects the uniform dispersion and overall performance of the material. 13 If the amount of nanowires is too small, the reinforcement effect may not be obvious, and the strength, flexibility and thermal insulation performance of the material cannot be effectively improved. 13 Excessive use of nanowires may lead to 13 The dispersion of nanowires is difficult, which affects the uniformity of the material. It will also increase the difficulty of processing and affect the overall performance of the material.

[0043] In a second aspect, the present invention provides a high-strength multi-layer thermal insulation material produced by the preparation method described in the first aspect of the present invention.

[0044] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments, and those skilled in the art may make various corresponding changes and deformations according to the present invention without departing from the spirit and essence of the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention.

[0045] Example 1

[0046] ① Using water, 1 part of phenolic fiber (diameter 200-500nm), 19 parts of zirconia fiber (1-3μm), 1 part of aluminum oxide nanosheets and 9 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fiber, zirconia fiber, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0047] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 2 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0048] ③ Lay 20 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 1 mm after the hot pressing mold is closed and pressed), and dry them at 200°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 500°C for 20 hours under an inert atmosphere (argon) to obtain a high-strength multi-layer thermal insulation material.

[0049] Example 2

[0050] ① Using water, 3 parts of phenolic fibers (diameter 500-1000nm), 17 parts of zirconia fibers (3-8μm), 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0051] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 500 nm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0052] ③ Lay 40 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 0.5 mm after the hot pressing mold is closed and pressed), and dry them at 240°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a high-strength multi-layer thermal insulation material.

[0053] Example 3

[0054] ① Using water, 4 parts of phenolic fibers (diameter 500-1000nm), 16 parts of zirconia fibers (5-10μm), 4 parts of aluminum oxide nanosheets and 1 part of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0055] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 1 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0056] ③ Lay 10 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 2 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a high-strength multi-layer thermal insulation material.

[0057] Example 4

[0058] ① Using water, 3 parts of phenolic fibers (diameter 300-800nm), 17 parts of zirconia fibers (3-8μm), 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0059] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 1 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0060] ③ Lay 20 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 1 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a high-strength multi-layer thermal insulation material.

[0061] Example 5

[0062] Embodiment 5 is substantially the same as Embodiment 4, except that:

[0063] ① Mix 3 parts of phenolic fiber (diameter 300-800nm), 17 parts of zirconium oxide fiber (3-8μm), 1.5 parts of potassium hexatitanate K2Ti6O 13Nanowires, 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconium oxide fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0064] Example 6

[0065] Embodiment 6 is substantially the same as Embodiment 4, except that:

[0066] ① Mix 3 parts of phenolic fiber (diameter 300-800nm), 17 parts of zirconium oxide fiber (3-8μm), 3 parts of potassium hexatitanate K2Ti6O 13 Nanowires, 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconium oxide fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0067] Example 7

[0068] Example 7 is substantially the same as Example 4, except that:

[0069] ① Mix 3 parts of phenolic fiber (diameter 300-800nm), 17 parts of zirconium oxide fiber (3-8μm), 0.5 parts of potassium hexatitanate K2Ti6O 13 Nanowires, 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconium oxide fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0070] Example 8

[0071] Embodiment 8 is substantially the same as Embodiment 4, except that:

[0072] ① Using water, 3 parts of phenolic fibers (diameter 300-800nm), 17 parts of zirconia fibers (3-8μm), 1.5 parts of titanium dioxide TiO2 nanowires, 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0073] Comparative Example 1

[0074] ① Using water, 3 parts of phenolic fibers (diameter 300-800nm), 17 parts of zirconia fibers (3-8μm), 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0075] ② A porous phenolic fiber cloth with a thickness of 1 mm and a pore size of 2 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0076] ③ Lay 10 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 2 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a multi-layer thermal insulation material.

[0077] Comparative Example 2

[0078] ① Using water, 3 parts of phenolic fibers (diameter 300-800nm), 17 parts of zirconia fibers (3-8μm), 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) are stirred and dispersed at a rotation speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of phenolic fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0079] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 3 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0080] ③ Lay 20 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 1 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a multi-layer thermal insulation material.

[0081] Comparative Example 3

[0082] ① Stir and disperse 20 parts of zirconia fibers (3-8 μm), 2 parts of alumina nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) with water at a speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of zirconia fibers, alumina nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0083] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 1 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0084] ③ Lay 20 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 1 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a multi-layer thermal insulation material.

[0085] Comparative Example 4

[0086] ① Stir and disperse 20 parts of zirconium oxide fibers (3-8 μm) and 10 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) with water at a speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of zirconium oxide fibers and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0087] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 1 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0088] ③ Lay 20 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of the preform is 1 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours. Then put them in an inert atmosphere furnace and carbonize them at 900°C for 10 hours under an inert atmosphere (argon) to obtain a multi-layer thermal insulation material.

[0089] Comparative Example 5

[0090] ① Stir and disperse 20 parts of zirconium oxide fibers (3-8 μm) and 10 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) with water at a speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of zirconium oxide fibers and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0091] ② A porous phenolic fiber cloth with a thickness of 10 μm and a pore size of 1 μm (the porosity of the porous phenolic fiber cloth is 60%) is laid flat in a papermaking device as a filter medium, and then the dispersed system obtained in step ① is papermade by the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth.

[0092] ③ Lay 20 layers of preforms layer by layer in a hot pressing mold with an internal accommodating space of 20 mm in thickness (the thickness of each layer of preform is 1 mm after the hot pressing mold is closed and pressed), and dry them at 300°C for 24 hours to obtain a multi-layer insulation material.

[0093] Comparative Example 6

[0094] ① Stir and disperse 20 parts of zirconia fibers (3-8 μm), 2 parts of alumina nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) with water at a speed of 4000 r / min for 35 minutes to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of zirconia fibers, alumina nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0095] ② Use papermaking equipment to paper the dispersed system obtained in step ① to obtain a fiber wet sheet with a thickness of 1 mm.

[0096] ③ 21 reflective screens (carbon fiber cloths) and 20 fiber wet sheets are alternately arranged, and after being molded at a pressure of 1 MPa for 60 minutes, they are sent into a high-temperature oven for high-temperature curing at 120°C for 24 hours to obtain a multi-layer thermal insulation material; wherein, the thickness of each carbon fiber cloth is 0.1 mm, and in the alternating arrangement, a fiber wet sheet is arranged between every two carbon fiber cloths, and the carbon fiber cloth and the fiber wet sheets are bonded by an aluminum phosphate aqueous solution (the mass fraction of aluminum phosphate contained in the aluminum phosphate aqueous solution is 20%).

[0097] Comparative Example 7

[0098] Comparative Example 7 is substantially the same as Example 4, except that:

[0099] ① Use water to stir and disperse 3 parts of carbon fibers (diameter 300-800nm), 17 parts of zirconia fibers (3-8μm), 2 parts of aluminum oxide nanosheets and 8 parts of aluminum dihydrogen phosphate solution (the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 30%) at a speed of 4000r / min for 35min to obtain a uniformly dispersed dispersion system; the sum of the mass percentages of carbon fibers, zirconia fibers, aluminum oxide nanosheets and aluminum dihydrogen phosphate contained in the dispersion system is 15%.

[0100] The present invention conducts bending strength, compressive strength (5% deformation) and 300°C thermal conductivity tests on the high-strength multi-layer thermal insulation materials prepared in each embodiment and the multi-layer thermal insulation materials prepared in each comparative example, and the results are shown in Table 1; It can be seen from Table 1 that the high-strength multi-layer thermal insulation materials prepared in each embodiment of the present invention have high strength and excellent thermal insulation performance.

[0101] Table 1: Mechanical and thermal performance results of the high-strength multi-layer thermal insulation materials prepared in each embodiment and the multi-layer thermal insulation materials prepared in each comparative example.

[0102]

[0103] The “parts” involved in the embodiments and comparative examples of the present invention all refer to “parts by weight”, and the unit may be, for example, “g” or “kg” or other weight units.

[0104] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-strength multi-layer thermal insulation material, characterized in that: The method comprises the following steps: (1) uniformly dispersing phenolic fiber, zirconium oxide fiber, aluminum oxide nanosheets and phosphate solution with water to obtain a dispersed system; (2) laying a porous phenolic fiber cloth flat in a papermaking device as a filter medium, and then papermaking the dispersed system through the papermaking device on which the porous phenolic fiber cloth is laid flat to obtain a preform; the preform comprises the porous phenolic fiber cloth and the papermaking material obtained on the porous phenolic fiber cloth; (3) The multi-layer preform is laid layer by layer in a shaping mold for shaping and drying, and then carbonized under an inert atmosphere to obtain a high-strength multi-layer thermal insulation material.

2. The preparation method according to claim 1, characterized in that: In step (1): The mass ratio of the zirconium oxide fiber to the phenolic fiber is (4-19):1; The mass ratio of the aluminum oxide nanosheets to the phosphate solution is (1-4):(1-9); and / or The phosphate solution is an aluminum dihydrogen phosphate solution, and the mass fraction of aluminum dihydrogen phosphate contained in the aluminum dihydrogen phosphate solution is 20-50%.

3. The preparation method according to claim 1, characterized in that: In step (1): The diameter of the zirconia fiber is 1 to 10 μm; and / or The diameter of the phenolic fiber is 200-1000nm.

4. The preparation method according to claim 1, characterized in that: In step (1): The dispersion speed is 4000-10000 r / min, and the dispersion time is 3-40 min.

5. The preparation method according to claim 1, characterized in that: In step (2): The pore size of the porous phenolic fiber cloth is 500nm to 2μm; and / or The thickness of the porous phenolic fiber cloth is 10-200 μm.

6. The preparation method according to claim 1, characterized in that: The thickness of the single-layer preform is 0.5 to 2 mm; and / or The thickness of the high-strength multi-layer heat-insulating material is 15 to 25 mm.

7. The preparation method according to claim 1, characterized in that: In step (3): The temperature of the shaping and drying is 200°C to 300°C.

8. The preparation method according to claim 1, characterized in that: In step (3): The carbonization temperature is 500-900° C., and the carbonization time is 10-20 hours.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (1): The dispersed system also contains potassium hexatitanate K2Ti6O 13 Nanowires; Preferably, the potassium hexatitanate K2Ti6O 13 The mass ratio of the nanowires to the aluminum oxide nanosheets is 1:(1-2).

10. A high-strength multi-layer thermal insulation material produced by the production method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Alumina / zirconia fiber composite thermal insulation material and preparation method thereof

    CN113981732A

  • Heat transfer suppression sheet, method of manufacturing heat transfer suppression sheet, and battery pack

    JP2023056748A